Some Estimates of the Maximum Modulus for Polynomials with Gaps (Analysis in Theory and Applications, 2020)
Let $p(z)$ be a polynomial of degree $n$ having some zeros at a point $z_0\in\mathbb{C}$ with $|z_0|